Answer:
Step-by-step explanation:
Let X be the no of customers who purchase atleast one item.
X is binomial since there are two outcomes and each customer is independent of the other.
a) Here n =10
Out of 10 customers we expect np = 3 customers to buy at least one item.
b) exactly 3 of the customers would purchase at least one item
=![P(X=3)=10C3(0.3)^3(0,7)^7\\=0.2668](https://tex.z-dn.net/?f=P%28X%3D3%29%3D10C3%280.3%29%5E3%280%2C7%29%5E7%5C%5C%3D0.2668)
c) the probability that no more than 3 customers would purchase at least one item
=![P(X\leq 3)\\= 0.6496](https://tex.z-dn.net/?f=P%28X%5Cleq%203%29%5C%5C%3D%200.6496)
Using the binomial distribution, it is found that there is a 0.125 = 12.5% probability of observing exactly 3 tails.
<h3>What is the binomial distribution formula?</h3>
The formula is:
![P(X = x) = C_{n,x}.p^{x}.(1-p)^{n-x}](https://tex.z-dn.net/?f=P%28X%20%3D%20x%29%20%3D%20C_%7Bn%2Cx%7D.p%5E%7Bx%7D.%281-p%29%5E%7Bn-x%7D)
![C_{n,x} = \frac{n!}{x!(n-x)!}](https://tex.z-dn.net/?f=C_%7Bn%2Cx%7D%20%3D%20%5Cfrac%7Bn%21%7D%7Bx%21%28n-x%29%21%7D)
The parameters are:
- x is the number of successes.
- n is the number of trials.
- p is the probability of a success on a single trial.
In this problem, considering 3 tosses of a fair coin, the parameters are n = 3 and p = 0.5.
The probability of 3 tails is P(X = 3), hence:
![P(X = x) = C_{n,x}.p^{x}.(1-p)^{n-x}](https://tex.z-dn.net/?f=P%28X%20%3D%20x%29%20%3D%20C_%7Bn%2Cx%7D.p%5E%7Bx%7D.%281-p%29%5E%7Bn-x%7D)
![P(X = 3) = C_{3,3}.(0.5)^{3}.(0.5)^{0} = 0.125](https://tex.z-dn.net/?f=P%28X%20%3D%203%29%20%3D%20C_%7B3%2C3%7D.%280.5%29%5E%7B3%7D.%280.5%29%5E%7B0%7D%20%3D%200.125)
0.125 = 12.5% probability of observing exactly 3 tails.
More can be learned about the binomial distribution at brainly.com/question/24863377
Answer:
∆pkl and ∆nkl
Step-by-step explanation:
Supplementary angles are two angles whose measures add up to 180° . The two angles of a linear pair , like ∠pkl and ∠nkl in the figure above, are always supplementary.
Answer:
-17x is the answer mark me brainliest
Quadratic Formula: (-b +/- sqrt(b^2 - 4ac)) / 2a
2x^2 - 3x = 12
2x^2 - 3x - 12 = 0
a = 2
b = -3
c = -12
(--3 +/- sqrt( (-3)^2 - 4(2)(-12) )) / 2(2)
3 +/- sqrt( 9 + 96 ) / 4
3 +/- sqrt(105) / 4
Answers:
, ![\frac{3 - \sqrt{105} }{4}](https://tex.z-dn.net/?f=%5Cfrac%7B3%20-%20%5Csqrt%7B105%7D%20%7D%7B4%7D)
Hope this helps!